The Association Between Genetic Variants, Pharmacokinetics, and Infliximab Efficacy in Pediatric Patients With Crohn's Disease in China - Hu, Wenhui; Feng, Yan; Ye, Ziqing; Tang, Zifei; Qian, Lai; Wang, Yuhuan; Huang, Ying (Frontiers in Pediatrics, 2021)
Background Infliximab is an effective therapy for Crohn′s disease (CD). However, response to anti‐TNF treatment is inconsistent. The aim of this study was to investigate the associations between genetic variants, pharmacokinetics and infliximab efficacy in pediatric patients with CD. Methods This retrospective observational study included patients with CD under infliximab therapy between August 2015 and December 2020. Demographics, laboratory tests, medication data and disease activity index were collected. Trough levels of infliximab (TLI) and antibodies to infliximab (ATI) were measured at week 14 and reactive drug monitoring was performed during follow-up. A total of 10 single nucleotide polymorphisms involved in the NF-κB mediated inflammatory response, and in pharmacokinetics and therapeutic response to infliximab were genotyped. Results A total of 62 pediatric CD patients were enrolled. Clinical remission (CR) rate was 69.4% and 63.2% at week 14 and week 30, respectively. TLI at week 14 was significantly independently associated with the CR at week 14 and mucosal healing (MH) at week 30 (P=0.007 and P=0.025, respectively). The optimal TLI threshold level capable to distinguish between CR group and non-CR group was 2.62 μg/mL (P<0.001, area under the curve=0.79, sensitivity 69.2%, specificity 78.9%), between MH and non-MH group was 3.34 μg/mL (P< 0.001, area under the curve=0.85, sensitivity 78.6%, specificity 79.4%). Rs3397 in TNFRSF1B was associated with time to ATI production in CD patients (P<0.001). Conclusions Higher TLI contributed to achieving MH. Genotyping rs3397 in TNFRSF1B may help identify patients who are prone to generate immunogenicity to drugs.